Patients resistant against PSMA-targeting α-radiation therapy often harbor mutations in DNA damage-repair-associated genes - Kratochwil, Clemens; Giesel, Frederik L.; Heußel, Claus Peter; Kazdal, Daniel; Endris, Volker; Nientiedt, Cathleen; Bruchertseifer, Frank; Kippenberger, Maximilian; Rathke, Hendrik; Leichsenring, Jonas; Hohenfellner, Markus; Morgenstern, Alfred; et al. (Journal of nuclear medicine, 2020)
Prostate-specific membrane antigen (PSMA)-targeting α-radiation therapy (TAT) is an emerging treatment modality for metastatic castration-resistant prostate cancer. There is a subgroup of patients with poor response despite sufficient expression of PSMA in their tumors. The aim of this work was to characterize PSMA-TAT-nonresponding lesions by targeted next-generation sequencing. Methods: Of 60 patients treated with 225Ac-PSMA-617, we identified 10 patients who presented with a poor response despite sufficient tumor uptake in PSMA PET/CT. We were able to perform CT-guided biopsies with histologic validation of the nonresponding lesions in 7 of these nonresponding patients. Specimens were analyzed by targeted next-generation sequencing interrogating 37 DNA damage-repair-associated genes. Results: In the 7 tumor samples analyzed, we found a total of 15 whole-gene deletions, deleterious or presumably deleterious mutations affecting TP53 (n = 3), CHEK2 (n = 2), ATM (n = 2), and BRCA1, BRCA2, PALB2, MSH2, MSH6, NBN, FANCB, and PMS1 (n = 1 each). The average number of deleterious or presumably deleterious mutations was 2.2 (range, 0-6) per patient. In addition, several variants of unknown significance in ATM, BRCA1, MSH2, SLX4, ERCC, and various FANC genes were detected. Conclusion: Patients with resistance to PSMA-TAT despite PSMA positivity frequently harbor mutations in DNA damage-repair and checkpoint genes. Although the causal role of these alterations in the patient outcome remains to be determined, our findings encourage future studies combining PSMA-TAT and DNA damage-repair-targeting agents such as poly(ADP-ribose)-polymerase inhibitors.
Published online Oct. 10,
Gesehen am 04.06.2020